Getting causes from powers - Mumford, Stephen; Anjum, Rani Lill. (Oxford : Oxford University Press, 2011)
Causation is everywhere in the world: it features in every science and technology. But how much do we understand it? Here the authors develop a new theory of causation based on an ontology of real powers or dispositions. They provide the first detailed outline of a thoroughly dispositional approach, and explore its surprising features.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Causation